Proteomic Analysis of Mycoplasma gallisepticum Vaccine Strain F - Collier , S.D.; Branton, S.L.; Evans, J.D.; Leigh, S.A.; Wan, X.F.; Cooksey, A.M.; Olanrewaju, H.A.; Pharr, G.T. (International Journal of Poultry Science, 2014)
The persistence and displacement abilities of the Mycoplasma gallisepticum vaccine strain F (F-strain) are well documented. Understanding the mechanism(s) of colonization and persistence of F-strain will aid in the current intervention strategies to diagnose and control MG infections in poultry. In the present study, phase partition and liquid chromatography along with electrospray mass spectrometry were used to evaluate the proteome of F-strain. A total of 586, 478 and 339 proteins were recognized from whole cell lysate (total protein), aqueous (cytosolic) and detergent phases (membrane), respectively. The proteins identified with the database searches were then grouped into three categories: (1) proteins from the membrane phase and found in the total proteins (TM); (2) proteins from the cytosolic phase and found in the total proteins (TC) and (3) proteins derived from the membrane and cytosolic phases and found in the total proteins (TMC). There were a total of 93 (33 as putative membrane proteins predicted by SOSUI), 207(13) and 79(6) proteins in the TM, TC and TMC, respectively. The identified proteins were distributed among John Craig Venter Institute (JCVI) categories, with the majority predicted to be involved in protein synthesis. Investigation of the Mycoplasma gallisepticum F-strain proteome may aid in the identification and characterization of F-strain proteins that are important in host colonization.